Revitalizing Religious Learning in Madrasah Through the Use of Technology - Andri Sungkowo; Munkizul Umam Kau; Muhammadong; Abdul Rozak; Yadi Suryadi (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2024)
In today's digital age, the use of information technology (IT) has become commonplace in many aspects of life, including in education. This study deals with the use of IT as a tool for revitalizing religious learning in madrasah with the aim of improving the effectiveness and quality of teaching learning processes. In the context of the madrasah, religious learning is often considered monotonous and less attractive, so the use of IT is expected to enrich teaching methods and expand students' access to diverse learning resources. This research uses literary methods by searching for references in accordance with the context of the research. Research results show that IT has great potential in supporting more interactive and enjoyable learning. Some examples of successful IT implementations include the use of interactive learning applications, social media for learning discussions, the creation of digital content such as educational videos and podcasts, and the implementation of Learning Management System (LMS) to facilitate student progress tracking. However, the study also identified barriers, such as infrastructure constraints, lack of training for teachers, and resistance to change on some sides. To overcome these obstacles, joint efforts between educational institutions, governments, and communities are needed to improve the availability of facilities, as well as conduct a comprehensive teacher training programme in the use of IT. Therefore, with adequate support and mature planning, IT can be a powerful tool in revitalizing religious learning in the madrasah, thereby producing a more dynamic, interactive, and adapted learning process